2020
DOI: 10.3390/info11020069
|View full text |Cite
|
Sign up to set email alerts
|

Theme Mapping and Bibliometrics Analysis of One Decade of Big Data Research in the Scopus Database

Abstract: Recently, the popularity of big data as a research field has shown continuous and wide-scale growth. This study aims to capture the scientific structure and topic evolution of big data research using bibliometrics and text mining-based analysis methods. Bibliographic data of journal articles regarding big data published between 2009 to 2018 were collected from the Scopus database and analyzed. The results show a significant growth of publications since 2014. Furthermore, the findings of this study highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…In the aspect of information security strategy research under the background of big data, the necessity of building a national competitive intelligence system based on information security is discussed [25,26], and the construction measures of the national competitive intelligence system based on information security are proposed. Intelligence literacy should be regarded as the core element of information security theory, and the solution of information security theory under the background of big data is explored [27,28]. Due to the complexity of information security, it is impossible to completely solve the problem of information security, either theoretically or technically.…”
Section: Related Workmentioning
confidence: 99%
“…In the aspect of information security strategy research under the background of big data, the necessity of building a national competitive intelligence system based on information security is discussed [25,26], and the construction measures of the national competitive intelligence system based on information security are proposed. Intelligence literacy should be regarded as the core element of information security theory, and the solution of information security theory under the background of big data is explored [27,28]. Due to the complexity of information security, it is impossible to completely solve the problem of information security, either theoretically or technically.…”
Section: Related Workmentioning
confidence: 99%
“…During this time, the concept has undergone significant changes that dramatically changed the term from a hype topic [7] to the foundation of most of the data-driven and data-intensive projects known today [4]. Despite that long lasting maturation and a highly active research community [8], no distinct and universally applied definition was found that precisely describes the nature and elements of that term [1]. Notwithstanding that, according to one of the most widely used definitions, Big Data "consists of extensive data sets -primarily in the characteristics of volume, variety, velocity, and/or variability -that require a scalable architecture for efficient storage, manipulation, and analysis" [9].…”
Section: Big Datamentioning
confidence: 99%
“…Despite that long-lasting maturation and a highly active research community [23], no distinct and universally applied definition was found that precisely describes the nature and elements of that term [17]. Notwithstanding that, according to one of the most widely used definitions, big data "consists of extensive datasetsprimarily in the characteristics of volume, variety, velocity, and/or variabilitythat require a scalable architecture for efficient storage, manipulation, and analysis" [24].…”
Section: Big Datamentioning
confidence: 99%